Synchronized metronome training induces changes in the kinematic properties of the golf swing - Sommer, M.; Häger, C.; Rönnqvist, L. (Sports Biomechanics, 2014)
The purpose of this study was to evaluate possible effects of synchronized metronome training (SMT) on movement dynamics during golf-swing performance, as captured by kinematic analysis. A one-group, between-test design was applied on 13 male golfers (27.5 ± 4.6 years old, 12.7 ± 4.9 handicap) who completed 12 sessions of SMT over a four-week period. Pre- and post-assessments of golf swings with three different clubs (4-iron, 7-iron, and pitching wedge) were performed using a three-dimensional motion capture system. Club velocity at three different swing phases (backswing, downswing, and follow-through) was measured and cross-correlation analysis of time-series signals were made on joint couplings (wrist-elbow-shoulder) of both arms, and between joints and the club, during the full golf swing. There were significantly higher cross-correlations between joint-couplings and concomitant changes of the associated phase-shift differences, as well as reduced phase-shift variability at post-test. No significant effect of SMT was found for the club velocities. We suggest that domain-general influences of SMT on the underlying brain-based motor control strategies lead to a more coordinated movement pattern of the golf-swing performance, which may explain previous observations of significantly improved golf-shot accuracy and decreased variability after SMT.